ANALISIS PERSEPSI TENTANG KB TERHADAP KEPUTUSAN PENGGUNAAN KONTRASEPSI PADA WANITA USIA SUBUR DI DESA PEKEN BELAYU TABANAN - Elisabet Sulastina; Kadek Widiantari; Ni Ketut Devi kaspirayanty; Siti Zakiah (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Reproductive health is a state of complete physical, mental, and social health in all matters related to the reproductive system, functions, and processes. This is a crucial aspect for women of childbearing age (WUS) aged 15–49 years to prevent health problems and achieve a quality life and family. The success of the Family Planning (FP) program is highly dependent on WUS's perception of the use of contraceptives. A positive perception, where WUS understand the benefits of FP for maternal and child health and plan family size. Conversely, negative perceptions or fear of side effects often reduce interest in using contraceptives. The purpose of this study was to determine the perception of FP on the decision to use contraception among WUS in Peken Belayu Village, Tabanan. This study used a quantitative method with an analytical design and a cross-sectional approach. The study sample consisted of 57 respondents taken using a simple random sampling technique. Data were analyzed univariately and bivariately using the Chi-Square test. The results showed that the majority of respondents had a positive perception of FP, namely 38 respondents (66.67%), and 41 respondents (71.93%) used contraceptives. Statistical analysis results showed a significant relationship between perceptions about family planning and contraceptive use decisions among women of childbearing age (WUS), with a p-value 0.001. This suggests that women of childbearing age who have positive perceptions about family planning are more likely to use contraception. Therefore, increased education and counseling are needed in the community.Keywords: Perception, Family planning,Women of Childbearing Age, Contraceptive Use.